Comparação de características miofuncionais e eletromiográficas de crianças obesas e eutróficas - Favero, Talita Cristina (2013)
Obesity is a chronic, complex and multifactorial etiology that determines several complications in childhood and adult age. Among the nutritional disorders, obesity is the one that creates the most musculoskeletal problems, inferring the importance of studies facing this population in the context of excessive weight gain and its contribution to a change in posture and function of the stomatognathic system. Thus, this study aimed to evaluate and compare the structures, functions and pattern of muscle electrical activity of the stomatognathic system of obese and eutrophic children through miofunctional evaluation and surface electromyography. Were evaluated 32 children between 6 and 12 years old, students from 1st to 6th grade in a public elementary school in the city of Santa Maria-RS. The children were divided into two groups according to their nutritional condition - 16 obese and 16 eutrophics. The variables studied included natural feeding, bottle feeding (artificial feeding), nutritional condition and miofunctional evaluation, according to the protocol MBGR; in addition, to electromyographic evaluation were evaluated the masticatory muscles (anterior temporal muscle, masseter and orbicularis oris) activities and maximal voluntary contraction (MVC), resting, chewing (directed and habitual) and swallowing. For statistical analysis were used frequency distribution, mean, median, first and third quartiles, t-Student Test, Chi-square, Fisher Exact and Wilcoxon, considering a significance level of p<0.05. Results related to orofacial evaluation showed that obese children received natural feeding for a shorter period of time and made more use of the bottle than eutrophic children. Mobility conditions, appearance and posture of the stomatognathic system were similar between groups. Changes of tone structures were observed in a greater number in the eutrophic group. Regarding the characteristics of chewing, it was observed that obese made greater number of chewing strokes and for a longer period of time than eutrophic individuals. There was no difference in speed and side of mastication compared between groups. As for electromyographic evaluation of masticatory muscles, the obese presented similar muscle activation compared to eutrophics during activities of MVC and rest (isometrics). However, for dynamic activities - chewing, swallowing and chewing directed - the obese had lower median muscle activation than eutrophic in most situations proposals in the activation period (on) and in the off period, with a statistically significant difference (p<0.05) for all muscle groups studied. Based on the results of this research, it was concluded that the nutritional status appears to have not much influence on the characteristics of the stomatognathic system in schoolchildren, but about their functions. These findings confirm the hypothesis that obese children, probably because of excessive facial fat, present changes in the conditioning of the masticatory muscles, which are reflected in the performance of the stomatognathic system’s functions.